Locally Advanced Oral Cavity Cancers: What Is The Optimal Care? - Rajab Alzahrani MD; Arwa Obaid MD; Hadi Al-Hakami MD; Ahmed Alshehri MD; Hossam Al-Assaf MD; Reem Adas MD; Eman Alduhaibi MD; Nabil Alsafadi MD; Suliman Alghamdi MD; Majed Alghamdi MD, FRCPC, DABR (Cancer Control, 2020)
Patients with oral cavity cancers often present late to seek medical care. Surgery is usually the preferred upfront treatment. However, surgical resection cannot be achieved in many cases with advanced disease without major impact on patient’s quality of life. On the other hand, radiotherapy (RT) and chemotherapy (CT) have not been employed routinely to replace surgery as curative treatment or to facilitate surgery as neoadjuvant therapy. The optimal care of these patients is challenging when surgical treatment is not feasible. In this review, we aimed to summarize the best available evidence-based treatment approaches for patients with locally advanced oral cavity cancer. Surgery followed by RT with or without CT is the standard of care for locally advanced oral cavity squamous cell carcinoma. In the case of unresectable disease, induction CT prior to surgery or chemoradiotherapy (CRT) can be attempted with curative intent. For inoperable patients or when surgery is expected to result in poor functional outcome, patients may be candidates for possibly curative CRT or palliative RT with a focus on quality of life.